Art and creativity for human development. Social representations of scenic and audiovisual artists in the state of Sonora, Mexico. - Gálvez Gonzalez, José Ricardo (UNIVERSIDAD DE SONORA, 2022)
This paper presents an analysis of the constituent elements for an intersubjective social construction and representation of reality about human development in relation to the artistic and creative practices of performing and audiovisual artists. Definitions on human development from the UNDP and contributions from Martha Nussbaum on democratic human development are taken as bases to relate it to the social representations of the artists participating in this study. An interpretive methodology was followed on narratives obtained from interviews with experienced artists in the region of the state of Sonora, Mexico. Among the main results, the importance of approaching art in the stages of secondary socialization stands out.